Success of Succinates and Prospects for Their Use in Critical Conditions - S. V. Sviridov; A. V. Butrov; V. V. Afanasyev; Yu. P. Orlov; A. Yu. Petrov (Антибиотики и Химиотерапия, 2024)
To date, preparations containing succinic acid (succinate) are widely known to specialists working in intensive care. Several such preparations have gained wide acclaim among anesthesiologists and resuscitators, namely: Reamberin, infusion solution — a crystalloid preparation containing 1.5% meglumine sodium succinate; Remaxol, infusional solution – a complex infusional solution containing, in addition to succinic acid, nicotinamide, inosine, as well as the aliphatic α-amino acid methionine (which serves in the body as a donor of methyl groups in S-adenosyl-methionine during the biosynthesis of choline, adrenaline, etc., and is also a source of sulfur during the biosynthesis of cysteine); Cytoﬂavin, a solution for intravenous administration, containing a complex of two vital vitamins necessary to provide a pool of coenzymes — B2 in the form of a highly water-soluble form of riboﬂavin mononucleotide and PP in the form of nicotinic acid amide, succinic acid, and inosine (riboxin), as well as succinic acid itself. However, some skeptics have not been convinced yet, they oppose the use of these medications in the treatment of critical conditions. The purpose of this article is to expand our views on the natural essence of succinates, their biological role in the human body, highlighting the existing experience of their use in critical conditions, as well as the possibility of their use in the future.